2003
DOI: 10.1148/radiol.2261012140
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Blood Volume Measurements in Experimental Tumors with Different Angiogenic Burdens—A Study in Mice

Abstract: Measurements of tumoral VVF at high-resolution MR imaging with long-circulating iron oxide are feasible and correlate with angiogenic burden in experimental tumor models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
89
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 19 publications
2
89
0
4
Order By: Relevance
“…Literature values of the fractional blood volume of orthotopic 9L tumors in the murine brain are scarce. Bremer et al (2003), using both in vivo MRI and nuclear imaging, reported a mean FV of 2% for D16 9L tumors implanted in the gluteal region of nude mice. Nomura et al (1994) also used nuclear imaging to measure blood volume and reported mean values of 12.4 mL/g for D8 9L tumors and 1.79 mL/g for the normal brain in Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…Literature values of the fractional blood volume of orthotopic 9L tumors in the murine brain are scarce. Bremer et al (2003), using both in vivo MRI and nuclear imaging, reported a mean FV of 2% for D16 9L tumors implanted in the gluteal region of nude mice. Nomura et al (1994) also used nuclear imaging to measure blood volume and reported mean values of 12.4 mL/g for D8 9L tumors and 1.79 mL/g for the normal brain in Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, vascular density can be measured in vivo with imaging techniques that map regional blood volume. Numerous studies have established a tight relationship between angiogenesis and regional blood volume (13)(14)(15)(16)(17), including in the brain where regional angiogenesis is coupled to regional cerebral blood volume (CBV) (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Furthermore, the local concentration of agent can be quantified because it is known to be proportional to the local increase ⌬R2* of the relaxation rate, considering the static dephasing regime in which diffusion effects are negligible (1). In diagnostic tumor imaging this linear relationship between concentration and ⌬R2* can be exploited for the quantitative imaging of tumor vascularity (2). In a similar application for tumor therapy, Nijsen et al (3) used the concentrationrelated R2* effect of paramagnetic radioactive holmiummicrospheres to monitor an intra-arterial radionuclide during liver-tumor treatment.…”
mentioning
confidence: 99%
“…In all of the above-mentioned applications, a method that combines real-time imaging and R2* mapping would facilitate direct therapy control and optimization, particularly for drug dosage determination. In the current paradigm, mapping is performed after imaging, and nonquantitative T2*-weighted images are used to dynamically monitor the delivery of the agent (2)(3)(4)(5). In some studies T2* quantification was performed once before and once after the delivery.…”
mentioning
confidence: 99%
See 1 more Smart Citation